![log_{2}(16) - log_{2}(2) log_{2}(16) - log_{2}(2)](https://tex.z-dn.net/?f=+log_%7B2%7D%2816%29++-++log_%7B2%7D%282%29+)
![answer \: fast \: answer \: fast \:](https://tex.z-dn.net/?f=answer+%5C%3A+fast+%5C%3A+)
Answers
Answered by
2
Answer:
3
Step-by-step explanation:
Given expression
log₂ 16 - log₂ 2
Use Quotient rule log a - log b = log a/b
= log₂ 16/2
= log₂ 8
= log₂ 2³
Use Product rule log a^m = mlog a
= 3log₂ 2
Since log_a a = 1
= 3 × 1
= 3
Therefore the answer of the expression is 3.
Similar questions